Records Management Practices in the Course of Globalization in European Union and Turkey - Külcü, Özgür (Information World, 2006)
The practices being realised in records and archive management in European Union during the accelerated globalisation after 1990’s was examined. In that respect entrepreneurial initiatives, projects, regulations, practice oriented models and standards, which appeared in the course of EU integration of Turkey were overviewed. Moreover, the approaches of the EU in the realm of the European integration process, which may have chances to effect the development of records and archival practices in Turkey, were discussed and evaluated.